Decreasing choline signal--a marker of phenylketonuria? - Dezortová, M; Hejcmanová, L; Hájek, M (Magma (New York, N.Y.), 1996)
We found a statistically significant increase in the N-acetylaspartate/choline-containing compounds (NAA/Cho) ratio in a group of 69 phenylketonuria (PKU) patients with a rise in echo time (TE) compared with a group of 35 age-matched controls. The absolute concentration of creatine did not differ significantly between patients and controls, but a significant difference was found for choline-containing compounds (1.33 mM in patients vs. 1.53 mM in controls, p < 0.0209). The change in NAA/Cho (for TE = 270 ms: 2.52 in patients vs. 1.96 in controls, p270 < 0.0001) can be explained by a significant difference in T2 values of choline compounds between patients and controls. This result shows that the difference in the ratios of signal intensities often used for the description of different pathologies can be explained not only by changes in the absolute metabolite concentration but also by changes in the mobility reflected by relaxation times.
Keywords: kreatin; Magnetic Resonance Spectroscopy; magnetická rezonanční spektroskopie; mladiství; Choline; studie případů a kontrol; Phenylketonurias; Adult; Aspartic Acid; dítě; Child; fenylketonurie; kyselina asparagová; Humans; biologické markery; cholin; Protons; dospělí; Biomarkers; Adolescent; Creatine; lidé; Case-Control Studies; protony